1987
DOI: 10.1007/bf00236315
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical and electrophysiological evidence for a direct projection from ammon's horn to the medial prefrontal cortex in the rat

Abstract: Following microinjection of wheat germ agglutinin-horseradish peroxidase (WGA-HRP) into the medial prefrontal cortex (defined as the neocortical area innervated by the thalamic mediodorsal nucleus) labelled cells were observed in the pyramidal layer of the CA1 field of Ammon's horn. Observations made using antidromic stimulation confirmed these results, and revealed that slow conduction velocity of the fibers of the hippocampal cells innervating the prefrontal cortex. Taken together, these data provide evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
139
1
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(155 citation statements)
references
References 18 publications
14
139
1
1
Order By: Relevance
“…This possibility is likely, because although the lesion boundaries in the schematic drawing in their study (Figure 1 in Flores et al 1996b) are similar to the boundaries of our lesion, their photomicrograph of the lesion (Figure 2) suggests that only more dorsal aspects of the mPFC have actually been damaged (i.e., area F2 or PrCm). It should be pointed out, moreover, that these dorsal prefrontal cortical regions do not receive direct projections from the hippocampus, as do the PL and IL (Swanson 1981;Jay et al 1989;Jay and Witter 1991;Ferino et al 1987;Laroche et al 1990). There is also no indication that the more dorsal mPFC would contribute more to the regulation of subcortical dopamine function than the ventral parts.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This possibility is likely, because although the lesion boundaries in the schematic drawing in their study (Figure 1 in Flores et al 1996b) are similar to the boundaries of our lesion, their photomicrograph of the lesion (Figure 2) suggests that only more dorsal aspects of the mPFC have actually been damaged (i.e., area F2 or PrCm). It should be pointed out, moreover, that these dorsal prefrontal cortical regions do not receive direct projections from the hippocampus, as do the PL and IL (Swanson 1981;Jay et al 1989;Jay and Witter 1991;Ferino et al 1987;Laroche et al 1990). There is also no indication that the more dorsal mPFC would contribute more to the regulation of subcortical dopamine function than the ventral parts.…”
Section: Discussionmentioning
confidence: 98%
“…19 , NO . 6 behaviors that implicate dysfunction of the PFC (Chambers et al 1996;Sams-Dodd et al 1997), possibly because neonatal damage of the ventral hippocampus disrupts neuronal development of the PFC, with which the hippocampus is closely interconnected (Swanson 1981;Ferino et al 1987;Jay et al 1989;Laroche et al 1990;Jay et al 1992;Carr and Sesack 1996). Because PFC dysfunction has been shown in rodents (Adler 1961;Lynch et al 1969;Iversen 1971;Pycock et al 1980;Kolb 1984;Reibaud et al 1984;Louilot et al 1989;Jaskiw et al 1991;Vezina et al 1991;Deutch 1992;Jaskiw and Weinberger 1992;King and Finlay 1995;Taber et al 1995;Karreman and Moghaddam 1996) and in primates (Kolachana et al 1995;Roberts et al 1994) to affect subcortical dopamine activity, the effect of the VH lesion on dopamine function might be indirectly mediated by an alteration at the level of the mPFC.…”
mentioning
confidence: 99%
“…The present work showed an age-related correlation of platelet NOS activity and cyclic GMP levels, and erythrocyte TBARS levels with the same biochemical assays in hippocampus and frontal cortex of rats. These two structures are implicated in learning and memory and are related through a direct excitatory pathway (Fuster 1991;Férino et al 1987;Swanson 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that ϳ30% of neurons exhibited turn-specific activities in cortical areas that project to the PFC . Furthermore, neurons in the ventral hippocampus exhibit placespecific firing (Jung et al, 1994;Poucet et al, 1994) and, via direct projections to the PFC (Swanson, 1981;Ferino et al, 1987;Jay and Witter, 1991), exert powerful influence on the discharges of PFC neurons (Siapas et al, 2005). If afferent neuronal activity is an important factor determining synchronous firing of PFC neu- Figure 5.…”
Section: Effects Of Afferent Neural Activitymentioning
confidence: 99%